Germination and viability of capilliconida of Neozygites floridana (Zygomycetes:Entomophthorales) under constant temperature, humidity and light conditions - Oduor, G.I.; Yaninek, John S.; Geest, L.P.S. van der; Moraes, G.J. de (Elsevier, 1996)
The germination of capilliconidia of Neozygites floridana on the cassava green mite, Mononychellus tanajoa, and the viability of these conidia collected on glass coverslips were studied at different temperatures, humidities (expressed as saturation deficit (SD), measured in mg Hg), and light conditions. Germination began within 2 hr of their attachment to the mites, at which time more than 66.0% of the conidia maintained at between 18 and 28°C, at SDs 0 and 0.2, and in the dark produced germ tubes. Percent germination pooled across all factors significantly increased from 15.7% after 2 hr to 28.2% after 6 hr and 45.0% after 14 hr. Germination at the extreme temperatures tested, 24.5% at 13°C and 14.8% at 33°C, was significantly lower than 40.0, 47.2, and 36.5% recorded at 18, 23, and 28°C, respectively. Percent germination increased with increasing humidity from 2.8% at SD 1.2 to 60.9% at SD 0. Although germination was observed when both light and dark conditions were tested, the 44.9% germination recorded under continuous darkness after 6 hr was significantly higher than 20.3% under continuous light. Rate of germination of capilliconidia declined with increasing storage time from 93.0% before storage to a pooled mean of 81.0% after 1 day and 3.5% after 10 days. Higher germination rates were maintained at lower temperatures. Whereas germination after 7 days did not exceed 8.0% at 28 and 33°C, it was 85.9 at SD 10 in the dark at 18°C. Germination at SD 10 was significantly higher (43.3%) than at SDs 6, 2, and 0 (between 31.34 and 34.95%). Continuous light reduced viability as an average of 47.1% of the conidia maintained in the dark germinated, compared to 23.5% of those in the light.